www.columbia.edu/itc/sipa/math/systems_linear.html

By setting first x and then y equal to zero it is possible to find the y intercept on ... If x = 0, then f(0) = 1 + .5(0) = 1. If y = 0, then f(x) = 0 = 1 + .5x. -.5x = 1. x = -2 ... If y = 0, then f(x) = 0 = 11 - 2x. 2x = 11. x = 5.5. The resulting data points are (0,11) and (5.5,0) ... From the graph it can be seen that these equations are equivalent.

jwilson.coe.uga.edu/EMT668/EMAT6680.Folders/Barron/unit/Lesson%205/5.html

Specifically, we graphed the two equations y = 2x + 5 and y = (-3/2)x + 2, and ... Now, we can set the right hand side of each equation equal to each other because they both equal y. ... x = 5y in the second equation, then x must also equal 5y in the first equation. .... Also, the point (0, 19/14) works, where x = 0 and y = 19/14.

www.khanacademy.org/math/cc-eighth-grade-math/cc-8th-systems-topic/cc-8th-systems-with-substitution/v/substitution-method-2

Learn to solve the system of equations y = -5x + 8 and 10x + 2y = -2 using ... x + y + z = –25 y = –8z x = 12z. And no, this isnt my homework. 5 Votes .... After you do so, you will find the B. Then substitute B in the first equation to find a. 6 Votes ..... y ^4 - 40y^2 + 144 = 0 ... How do I solve y=2x+7 and y=9x+8 using substitution?

www.montereyinstitute.org/courses/DevelopmentalMath/COURSE_TEXT2_RESOURCE/U14_L2_T1_text_final.html

You solve one equation for one variable and then substitute this expression ... Equation B gives you the value of y, y = 2, so you can substitute 2 into Equation A for y ... Equation B tells us that x = y + 5, so it makes sense to substitute that y + 5 ... original equations. y = 3x + 6. 0 = 3(−2) + 6. 0 = −6 + 6. 0 = 0. TRUE. −2x + 4y = 4.

www.themathpage.com/alg/equation-of-a-line-2.htm

Example 1. Calculate the value of x when y = 0, that is, find the x-intercept of y = 2x + 10. Solution. On putting y = 0, we have to solve the equation,. 2x + 10, = 0. We have: 2x, = −10. x, = −5. ... a) When we have the equation of a straight line, how do we find the ... the same. Find the intercepts by putting x -- then y -- equal to 0.

www.algebra.com/algebra/homework/Linear-equations/Linear-equations.faq.question.159004.html

2x+y<10 x>0,y>0 .... x+y<8 -x -x ______. Y<-x+8 2x+y<10 -2x -2x ______ y<-2x+ 10 .. i need to graph this but i do not know how to do it. ... for both equations to be equal with the same values of x and y in each, x must = 2 and y must = 6. that would be .... then x + y < 8 becomes .5 + 8 which is not < 8 so it fails the test. let x = 6 ...

www.rasmus.is/uk/t/F/Su52k03.htm

How do we set about finding the points in which two graphs y = f(x) and y = g(x) intersect? ... We calculate it by solving the equation f(x) = 0 . ... Solve the equation x2 − 2x − 3 = 2x − 3 first graphically, then algebraically. ... Example 5 ... definition of a logarithm we can see that x = 1 makes both sides of the equation equal to 0 ...

www.purplemath.com/modules/syseqgen4.htm

As before, I'll set these equations equal, and solve for the values of x: ... Since the first equation is already solved for y, I will plug "–x – 3" in for "y" in the second equation, and solve ... y = (1/2)x – 5 = (1/2)(5/2) – 5 = 5/4 – 20/4 = – 15/4 = –3.75 ... y = –x + 2. Then: xy = 1 x(–x + 2) = 1 –x2 + 2x = 1 –x2 + 2x – 1 = 0 x2 – 2x + 1 = 0

www.analyzemath.com/math_questions/math_questions_2_sol.html

... Log(x), then f -1(x) = Solution y = Log(x) if and only if x = 10 y. Interchange x and y y = 10 x. Hence ... The vertex of the graph of y = 2x 2 + 8x - 3 is given by. Solution ... The quadratic equation whose roots are at x = 3 and x = 5 is given by .... If Pi < x < 3 Pi/2, then sin(x) can be expressed in terms of tan(x) as follows. A. sin(x) ...

dl.uncw.edu/digilib/mathematics/algebra/mat111hb/izs/asolve/asolve.html

Square Root Principle. If x2 = k, then x = ± sqrt(k). Example 2. x2 - 9 = 0. ... In some cases the equation can be solved by factoring, but the factorization is not obvious. ... Now use a graphing utility to graph y = 2x2 + 6x - 5, and trace the graph to find ... x and a quadratic polynomial equal to 0, so we have two simpler equations.